DOMINANT CATCH OF SEA CUCUMBER IN DATU ISLAND (SCOTT REEF) AUSTRALIA FOR THE INCOME - Ralph Thomas Mahulette; Anthony Sisco Panggabean (Indonesian Fisheries Research Journal, 2010)
TypeS of Sea cucumbers or trepang which have important ecOnomic value and consumed were from'the genera Holothuria, Stichopodidae, and Thelenota. Sea cucumbers catch by Indonesian fishermen are not only done in Indonesian waters but also to reach the waters of Datu lsland (scott reef), which is Box 74 MoU region.